Protective Immunity against Secondary Poxvirus Infection Is Dependent on Antibody but Not on CD4 or CD8 T-Cell Function - Panchanathan, Vijay (American Society for Microbiology, 2006)
Renewed interest in smallpox and the need for safer vaccines have highlighted our lack of understanding of the requirements for protective immunity. Since smallpox has been eradicated, surrogate animal models of closely related orthopoxviruses, such as ectromelia virus, have been used to establish critical roles for CD8 T cells in the control of primary infection. To study the requirements for protection against secondary infection, we have used a prime-challenge regime, in which avirulent ectromelia virus was used to prime mice that were then challenged with virulent ectromelia virus. In contrast to primary infection, T cells are not required for recovery from secondary infection, since gene knockout mice deficient in CD8 T-cell function and wild-type mice acutely depleted of CD4, CD8, or both subsets were fully protected. Protection correlated with effective virus control and generation of neutralizing antibody. Notably, primed mice that lacked B cells, major histocompatibility complex class II, or CD40 succumbed to secondary infection. Thus, antibody is essential, but CD4 or CD8 T cells are not required for recovery from secondary poxvirus infection.